Measuring women's empowerment in fragile settings: Practical guidance and notes from the field - Ambler, Kate; Bloem, Jeffrey R.; Becquey, Elodie; Dione, Malick; Diop, Loty; Gelli, Aulo; Heckert, Jessica; Kosec, Katrina; Kyle, Jordan; Lambrecht, Isabel B.; Mardonova Tolibkhonovna, Mohru; Misra, Rewa S.; et al. (CGIAR System Organization, 2024)
Women’s economic empowerment includes the ability to participate in existing markets, access and control the use of productive resources, obtain opportunities for decent work, control the use of time, and the ability to participate in decision making within households and communities (United Nations 2018). Increasing women’s economic empowerment is relevant to several sustainable development goals (i.e., to achieve gender equality, promote full and productive employment and decent work for all, and reduce existing inequalities). Given all of this, accurately measuring women’s empowerment systematically across a variety of settings is imperative. As such, studying innovations in measuring women’s agency, empowerment, or decision-making power is an active area of research (Malapit et al. 2019; Donald et al. 2020; Laszlo et al. 2020; Buvinic et al. 2020; Quisumbing et al. 2023; Jayachandran et al. 2023).